Is climate-smart conservation feasible in Europe? Spatial relations of protected areas, soil carbon, and land values. Issue 57 (March 2016) - Jantke, Kerstin; Müller, Jana; Trapp, Natalie; Blanz, Benjamin
Graphical abstract: Highlights: Biodiversity conservation and climate change mitigation can be effectively linked. Possible sites show high biodiversity value, high carbon content and low land value. Europe provides a high potential for cost-effective and climate-smart conservation. Abstract: The expectations on protected areas to deliver not only biodiversity conservation but also to provide an array of different ecosystem services rise. Sequestration and storage of carbon are promising services that protected areas may provide. This study integrates spatially explicit data on terrestrial Natura 2000 sites, soil organic carbon, and agricultural land values to estimate the potential for climate-smart conservation planning in the European Union. The objectives of this study are to analyse spatial relations between protected areas soil carbon content, and land values on the European Union's land area as well as to locate and quantify the proportion of land with high carbon and low economic value within and outside protected areas. We apply a unique interdisciplinary framework with methods ranging from analyses based on geographical information systems, agricultural economics to statistics. Findings indicate that there is a significant overlap between Natura 2000 sites and regions with high carbon content across Europe. Statistical analyses show that carbon-rich regions have significantly lower land values than other areas. Our results suggest that biodiversity protection and mitigation of climate change through conservation of soil carbon could be simultaneously achieved in Europe's protected areas and beyond. We conclude that there is a notable potential for climate-smart conservation in Europe that needs further investigation.